ZAKAT DAN WAKAF SEBAGAI PILAR DALAM SISTEM PEREKONOMIAN NASIONAL - Nasution, Ph.D, Mustafa Edwin (Fakultas Ekonomi, UIN Maliki Malang, 2006)
In Islamic teaching, philanthropy plays a significant role which is equal to other worships. It can be seen through the zakat position in arkanul Islam that hold the 3rd rank after syahadah and sholat. Zakat and wakaf are not only the parts of Islamic Philanthropy aimed to make poor people well improved, but also the parts of state’s policy that can be used to support the development of economy.